Influence of aluminum oxide nanoparticles on the physical and mechanical properties of wood composites - Kumar, Anuj; Gupta, Arun; Sharma, Korada Viswanatha; Suriati, Ghazali (North Carolina State University, 2013)
Aluminum oxide nanoparticles were used as nanofillers in urea-formaldehyde (UF) resin and prepared for medium density fiberboards (MDF). The nanofillers composed weight percentage of the UF resin. The thermal and viscoelastic properties were studied using differential scanning calorimetry and dynamic mechanical analysis. The H value of the UF resin showed an increase with increasing nanoparticle concentration. The core temperature during hot pressing increased with the addition of nanofillers. The formaldehyde emissions from MDF decreased with an increase in the concentration of nanofillers. The internal bonding strength and the modulus of rupture of boards were improved significantly after nanoparticle loading.